Segurança na administração de medicamentos por via sonda na pessoa idosa: construção e validação de vídeo educativo - Nóbrega, Fernanda de Medeiros (2023)
Introduction: The aging process occurs gradually and is associated with a global decrease in the individual's functional capacity. At this stage of life, difficulty eating autonomously, inability to move and the presence of illnesses increase the likelihood of using tubes as a form of nutritional assistance. Individuals belonging to this age group show an increase in the prevalence of non-transmissible chronic diseases, requiring the use of pharmacological therapy for control. Therefore, the use of medication by tube becomes a common practice, but it faces several challenges related to its administration. To overcome these obstacles, it is necessary to adopt an interprofessional approach to ensure the proper administration of tube medications in the elderly. Objectives: To investigate the scientific evidence on the administration of medication by tube in the elderly; build and validate an educational video on the safety of administering medication through a tube in the elderly. Method: This is a methodological study, structured in three stages: the first stage was a scope review with a search for scientific articles in the databases and virtual libraries Cochrane, Medical Literature Analysis and Retrieval System On-line (MEDLINE/PubMed), Scielo and Scopus. To construct the guiding question, the Population, Concept and Context (PCC) strategy was used, being P for population (elderly person), C for concept (administration of medication) C for context (using enteral nutrition). Having as descriptors in Portuguese and English: elderly, enteral nutrition, drug use, food-drug interactions, drug interactions, pharmacokinetics, pharmacological actions and catheter obstruction. In the second stage, a video was produced on safety in the administration of medication by tube in the elderly. And in the last step, this educational technology was validated by a committee of judges. Results and discussion: In the scope review, 15 studies were selected that addressed successful experiences, problems associated with the administration of medication through a tube in the elderly and training that generated uniformity in clinical practice. Only one article was produced in Brazil, between the years 2018 to 2022. The educational video was constructed, bringing the hospital discharge of the elderly person using a probe, seeking to reach nursing professionals, the elderly person, caregivers and family members, in order to raise awareness of the correct practices in the administration of medication through this route, ensuring patient safety. This video was validated by a panel of judges with a content validation index of 1,00. To meet the judges' considerations, adjustments and additions were made in the production of the final educational video. Final considerations: The construction of an educational video on safety in the administration of medication by tube in the elderly, whose target audience are nursing professionals, the elderly, caregivers and family members, contributed to bring more scientific knowledge related to this theme, in addition to promoting a transition from hospital care to home care ensuring the safety of medication administration via tube in the elderly.